2015
DOI: 10.1021/jp508947f
|View full text |Cite
|
Sign up to set email alerts
|

Intrinsic and Dynamical Reaction Pathways of an Excited State Proton Transfer

Abstract: The detailed knowledge of excited state proton transfer mechanisms in complex environments is of paramount importance in chemistry. However, the definition of an effective reaction coordinate and the understanding of the driving force of the reaction can be difficult from both the experimental and the theoretical points of view. Here we analyzed by theoretical approaches the mechanism and the driving forces of the excited state proton transfer reaction occurring between the 7-hydroxy-4-(trifluoromethyl)coumari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
40
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 42 publications
2
40
0
Order By: Relevance
“…From the electronic point of view, the reorganization of the electronic density upon excitation and thus the degree of charge transfer associated to a given electronic excitation can be measured using simple descriptors such as the D CT index previously introduced and applied also to ESPT systems by some of us …”
Section: Resultssupporting
confidence: 60%
See 1 more Smart Citation
“…From the electronic point of view, the reorganization of the electronic density upon excitation and thus the degree of charge transfer associated to a given electronic excitation can be measured using simple descriptors such as the D CT index previously introduced and applied also to ESPT systems by some of us …”
Section: Resultssupporting
confidence: 60%
“…Current computational approaches can be helpful in the characterization of the ES phenomena, due to the possibility of clearly pointing out and analyzing the different factors affecting a particular path on the ES potential energy surfaces (ES‐PESs) . In this respect, the use of electronic‐density‐based indexes has demonstrated a valid contribution to the analysis of the charge transfer character of a given transition and in the characterization of ESPT reactions …”
Section: Introductionmentioning
confidence: 99%
“…The activation energy for the proton transfer computed in solution (Δ E # ) is computed to be 1.9 kcal/mol, as expected larger than what previously reported at the TD‐B3LYP/6‐31 + G(d,p) level of theory (0.25 kcal/mol). Nonetheless, in SAC‐CI results, a plateau in the R OH = 1.10–1.30 Å range (corresponding to the transition state region) is found.…”
Section: Resultssupporting
confidence: 50%
“…To decouple structural from electronic effects, the same geometries will be firstly considered for all ES calculations performed using DFs. In particular, the structures obtained using a global hybrid (GH) have been considered as it has been previously shown that this level of theory enables to correctly describe the reaction profile in solution when compared to available experimental data …”
Section: Introductionmentioning
confidence: 99%
“…Not surprisingly, these methodologies have been extensively applied to study ESPT reactions . Moreover, the same approach can be applied, with due care, to the analysis of nonradiative events …”
Section: Introductionmentioning
confidence: 99%